Socioemotional Exchanges Between Men and Women in Heterosexual Relationships - Gaines, Stanley O.; Sedikides, Constantine (Frontiers in Psychology, 2022)
We examined affection-giving, affection-denying, respect-giving, and respect-denying behaviors among men and women in heterosexual relationships. In a pilot study (N = 106 couples), although we had expected the latent variables of affectionate and respectful behaviors to emerge from exploratory factor analyses, we obtained the latent variables of socioemotional rewards and costs instead. In the main study (initial N = 182 couples), we replicated the factor patterns of socioemotional rewards and costs in confirmatory factor analyses. Moreover, we entered (final N = 177 couples) men’s and women’s self-reported narcissism alongside men’s and women’s socioemotional rewards and costs, as reported by partners, into a dyadic model that we tested via covariance structure analyses. Results revealed that, although men and women reciprocated rewards as well as costs (and correlations between individuals’ rewards and costs were negative), narcissism was not reflected in the patterns of reciprocity. (Men’s and women’s narcissism were positively related.) We discuss implications for studies of relationship processes as two-person group dynamics.